Pengawasan pada kualitas asuhan keperawatan dan pelaksanaan perawat dalam pemberian asuhan keperawatan - Eka Yudha Chrisanto; Triyoso Triyoso; Bina Riani (Holistik Jurnal Kesehatan, 2021)
Supervision in nursing care quality and evidence in practice among staff nursesBackground: In achieving service performance, the number of outpatient visits in 2013 was 35,120 people or an average of 119 people per day or decreased by 18.5% and in 2016 23,449 people with an average of 95 people per day or a decrease of 19.1%, which means there is a decrease in patient visits at the hospital. In hospitalization, 2013 amounted to 12,219 people and in 2016 amounted to 10074 people which means a decrease of 17.5%.Purpose: To determine the relationship between supervision in nursing care quality and evidence in practice among staff nurses.Method: Type of quantitative research with Cross Sectional approach. Target in the research of all nurses, the place of research will be carried out in the Perinatology room of the Regional General Hospital Dr. H. Abdul Moeloek Lampung Province. the research time is planned for April - May 2019. Results: The majority of respondents with a good performance of 67.9% and the majority of respondents with good supervision that is as much as 58.0% There is a relationship of supervision with the performance of nursing care for nurses in children's with a P-value of 0.001 and OR: 5,484Conclusion: There is a relationship of supervision with the performance of nursing care for nurses in the inpatient room. The performance of nursing care for nurses must be developed, not only by nurses in person but need support from various related parties through good relations, mutual trust, and mutual understanding between various systems in hospital organizationsKeywords: Supervision; Nursing care quality; Evidence in practice; Staff nurses.Pendahuluan: Dalam pencapaian kinerja pelayanan, jumlah kunjungan pasien rawat jalan Tahun 2013 sebanyak 35.120 orang atau rata-rata perhari 119 orang atau turun sebesar 18,5% dan di tahun 2016 sebanyak 23.449 orang dengan rata – rata perhari 95 orang atau turun sebesar 19,1%, yang artinya terjadi penurunan kunjungan pasien di Rumah Sakit. Pada rawat inap, tahun 2013 sebesar 12.219 orang dan tahun 2016 sebesar 10074 orang yang artinya mengalami penurunan sebesar 17,5%.Tujuan: Untuk mengetahui hubungan supervisi kepala ruangan dengan kinerja asuhan keperawatan pada perawat di ruang rawat inap anak.Metode: Jenis penelitian kuantitatif dengan pendekatan Cross Sectional. Sasaran dalam penelitian seluruh perawat, tempat penelitian akan dilaksanakan di ruang Perinatologi.Hasil: Sebagian besar responden dengan kinerja baik sebesar 67,9% dan sebagian besar responden dengan supervise baik yaitu sebanyak 58,0%. Ada hubungan supervisi dengan kinerja asuhan keperawatan pada perawat di ruang rawat inap anak dengan nilai P-value 0,001 dan OR: 5.484Simpulan: Ada hubungan supervisi dengan kinerja asuhan keperawatan pada perawat di ruang rawat inap anak. Kinerja asuhan keperawatan pada perawat harus dikembangkan, tidak hanya oleh perawat secara pribadi tetapi perlu dukungan dari berbagai pihak terkait melalui hubungan yang baik, saling percaya, dan saling pengertian antara berbagai sistem didalam organisasi rumah sakit.